2011
DOI: 10.1109/mcom.2011.6094024
|View full text |Cite
|
Sign up to set email alerts
|

Spatial modulation for multiple-antenna wireless systems: a survey

Abstract: Multiple-antenna techniques constitute a key technology for modern wireless communications, which trade-off superior error performance and higher data rates for increased system complexity and cost. Among the many transmission principles that exploit multiple-antenna at either the transmitter, the receiver, or both, Spatial Modulation (SM) is a novel and recently proposed multipleantenna transmission technique which can offer, with a very low system complexity, improved data rates compared to Single-Input-Sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
379
0
23

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 736 publications
(404 citation statements)
references
References 15 publications
2
379
0
23
Order By: Relevance
“…Moreover, the single-RF design is capable of employing a low-complexity single-stream maximum-likelihood (ML) detector and offering an increased energy efficiency compared with multiple-RF-chain-based schemes. As a result, SM constitutes a promising transmission candidate for multiple-input-multiple-output (MIMO) design [7][8][9]. It is found that the performances (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the single-RF design is capable of employing a low-complexity single-stream maximum-likelihood (ML) detector and offering an increased energy efficiency compared with multiple-RF-chain-based schemes. As a result, SM constitutes a promising transmission candidate for multiple-input-multiple-output (MIMO) design [7][8][9]. It is found that the performances (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2, when Nt=4, Nr=1, and M=2 (BPSK) [9] . Let      with       and    be the transmitted message.…”
Section: Spatial Modulation (Sm)mentioning
confidence: 99%
“…where  • for   and  is the decision metric defined in what follows: Euclidean distance between signals x and y [9] . Nsub=4 and M=2, every log    log   bits are transmitted at each time instant and grouped as follows [4] :…”
Section: Spatial Modulation (Sm)mentioning
confidence: 99%
“…Recently, spatial modulation (SM) [1] transmission scheme in multiple-input multiple-output (MIMO) systems has drawn substantial attentions [2][3]. The SM-MIMO systems exploiting both spatial dimension and amplitude and phase modulation (APM) to convey information bits differ from the conventional approach which uses only APM to convey information.…”
Section: Introductionmentioning
confidence: 99%